The Role of Local Government in Coal Transition: The Case of Rural Alberta - Mateus, Martin; Markey, Sean; Ryser, Laura; Halseth, Greg; Hallstrom, Lars (Canadian Planning and Policy / Aménagement et politique au Canada, 2024)
Since the 1980s, Canadian municipalities have experienced pressures due to legislative/policy reforms and the downloading of responsibilities from senior governments. This shift has affected daily operations as municipalities struggle with outdated financial and jurisdictional structures. Such pressures have been exacerbated in Alberta by provincial and federal ‘coal phase-out’ policies, as the coal industry has historically been a primary source of revenue for some communities. In response, municipalities have engaged in processes to generate revenue, maintain service levels, and diversify their economies. This research, in Parkland County and Forestburg, Alberta, explores impacts and responses associated with top-down policy change. Results indicate that senior government supports were inadequate in the delivery of effective transition supports, which created challenges for local governments grappling with transition impacts. Municipalities have developed innovative and entrepreneurial solutions in transition, but the research outlines lessons and policy recommendations to better integrate municipalities into future transition policy and programs.